PENGARUH PROSES PENGUKUSAN PADA DAUN UBI JALAR VARIETAS UNGU (Ipomoea batatas L.) TERHADAP KADAR B-KAROTEN DENGAN METODE SPEKTROFOTOMETRI UV-Vis - Desi Sri Rejeki; Agung Nur Cahyanta; Isna Azzah Arfiyani (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2021)
B-carotene is a very potential source of vitamin A and has the highest vitamin A activity of all known carotenoids. B-carotene in purple sweet potato varieties fulfils the needs of vitamin A and works as an antioxidant in reducing the effects of free radicals. The research aimed to determine the levels of B-carotene in fresh, and steamed purple sweet potato varieties by spectrophotometry UV-Vis. The extraction used liquid maceration method with n-hexane, acetone, and ethanol as a solvent with ratio 2:1:1. The method used for qualitative analysis was TLC with eluents n-hexane: acetone: ethanol by comparison 1:1:2 by silica gel plate as stationary phase. The qualitative analysis results showed that the value of Rf in fresh purple sweet potato leaves were 0.81 and steamed purple sweet potato leaves were 0.83. The maximum B-carotene wavelength was 450.5nm. The quantitative analysis results stated linear regression equation y=-8+1.27x and the correlation coefficient of 0.997. B-carotene levels of fresh and steamed purple sweet potato leaves were respectively 6.4036 yg/gram and 6.3721 yg/gram. The levels obtained were analysed by Independent Sample T Test with a significance level of 95%. The Independent Sample T Test results showed that there was an effect on the process of boiling and steaming on B-carotene level in purple sweet potato leaves. In conclusion, the B-carotene level of sweet potato leaves in the steaming process was better than boiling process.